2021
DOI: 10.3389/fimmu.2021.606146
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MICA in Zero Hour Biopsies Predicts Graft Survival After Liver Transplantation

Abstract: In search for novel biomarkers to assess graft quality, we investigated whether defined candidate genes are predictive for outcome after liver transplantation (LT).Zero-hour liver biopsies were obtained from 88 livers. Gene expression of selected candidate markers was analyzed and correlated with clinical parameters as well as short and long-term outcomes post LT. Whereas both, the calculated Eurotransplant Donor-Risk-Index and the donor body mass index, had either a poor or no predictive value concerning seru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The thermal cycler conditions were as follows: 30 s at 95.0 °C for cDNA denatured, followed by 40 cycles of 15 s at 95 °C and 60 °C for the 34 s. Verification of specific product amplification was performed by dissociation curve analysis. The mRNA relative expression was calculated by the 2^ −ΔCt method with Gapdh used as an internal control [ 16 , 17 ].Primer sequences for each gene were listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The thermal cycler conditions were as follows: 30 s at 95.0 °C for cDNA denatured, followed by 40 cycles of 15 s at 95 °C and 60 °C for the 34 s. Verification of specific product amplification was performed by dissociation curve analysis. The mRNA relative expression was calculated by the 2^ −ΔCt method with Gapdh used as an internal control [ 16 , 17 ].Primer sequences for each gene were listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, donors with low Nrf2 mRNA levels (n=8) were significantly older than those with high levels, suggesting that older grafts experienced severe IRI 39 and inferior graft quality. Additionally, Resch et al 40 reported that high gene expression of the major histocompatibility complex class 1 related chain A (MICA) mRNA in zero hour biopsies (n=88) was associated with mild graft injury and prolonged graft survival. During LT, MICA had an important role in linking the innate and adaptive immune responses via interacting with NK cells, mucosal-associated invariant T, CD8+T cells, et al 40 miR-22, a regulator of a series of pathways such as cell cycle, metabolism and kinase signaling, is relevant to cell survival, glucose metabolism, and protein translation.…”
Section: Rnasmentioning
confidence: 99%
“…Additionally, Resch et al 40 reported that high gene expression of the major histocompatibility complex class 1 related chain A (MICA) mRNA in zero hour biopsies (n=88) was associated with mild graft injury and prolonged graft survival. During LT, MICA had an important role in linking the innate and adaptive immune responses via interacting with NK cells, mucosal-associated invariant T, CD8+T cells, et al 40 miR-22, a regulator of a series of pathways such as cell cycle, metabolism and kinase signaling, is relevant to cell survival, glucose metabolism, and protein translation. 41 Khorsandi et al 41 rereported that low expression of graft miR-22 was associated with the incidence of PNF after DCD LT (n=21).…”
Section: Rnasmentioning
confidence: 99%
“…Veri cation of speci c product ampli cation was performed by dissociation curve analysis. The mRNA relative expression was calculated by the 2^-ΔCt method with Gapdh used as an internal control [16,17]. Primer sequences for each gene were listed in Supplementary Table 1.…”
Section: Shdsyy-2021-y0688)mentioning
confidence: 99%